2004
DOI: 10.1002/pam.20029
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bicycle helmet legislation on bicycling fatalities

Abstract: A number of states passed legislation in the 1990s requiring youths to wear helmets when riding bicycles. The effect of this legislation on bicycling fatalities is examined by subjecting data from the Fatality Analysis Reporting System to a panel analysis, using a control-group methodology. A helmet law reduces fatalities by about 15 percent in the long run, less in the short run. There is no evidence of spillover effects (to adults) or substitution effects (youths choosing other methods of transportation) ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 35 publications
5
24
0
Order By: Relevance
“…Since our data reveal a small number of motorcycle fatalities in many states and years, employing count models may be more appropriate than using fatality rates in this case (Grant and Rutner, 2004;Morrisey and Grabowski, 2005). Given the nature of the underlying data, we also estimate a model for fatal injury counts using a conditional fixed-effects count data technique proposed by Hausman et al (1984).…”
Section: Methodsmentioning
confidence: 99%
“…Since our data reveal a small number of motorcycle fatalities in many states and years, employing count models may be more appropriate than using fatality rates in this case (Grant and Rutner, 2004;Morrisey and Grabowski, 2005). Given the nature of the underlying data, we also estimate a model for fatal injury counts using a conditional fixed-effects count data technique proposed by Hausman et al (1984).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, if this estimate is negative and comparable in the target and control groups, both may be caused by omitted factors, and our conclusions are weakened accordingly. This estimation strategy, adopted in recent studies of traffic safety legislation such as Dee and Evans (2001) and Grant and Rutner (2004), has additional power here because of the existence of several reasonable control groups, described below.…”
Section: Empirical Methodsmentioning
confidence: 99%
“…Earlier crash-trend analyses using FARS data suggested that State helmet-use laws for children reduce child bicycle fatalities by about 15% in the long run (Grant & Rutner, 2004). Wesson et al (2008) examined before and after trends in child and adult fatalities in Ontario, Canada following implementation of a law requiring helmets for riders under 18 years of age.…”
Section: Childrenmentioning
confidence: 99%